2013
DOI: 10.1521/psyc.2013.76.2.150
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization-Based Treatment for Postpartum Depressed Mothers and Their Babies: Rationale, Principles, and Preliminary Follow-Up Data

Abstract: This paper describes the rationale and treatment principles of a mother-infant unit for severely depressed mothers and their infants in Flanders (Belgium). The unit integrates systemic, psychodynamic, and cognitive behavioral treatment approaches, and aims at improvements on three levels: (1) improving mood and interpersonal relationships in depressed mothers, (2) fostering a positive mother infant relationship, and (3) establishing a supportive environment outside the treatment setting for both mother and inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(76 citation statements)
references
References 62 publications
2
72
0
Order By: Relevance
“…However the French version has more details on paternal disorders, drug treatments and past-history of both parents (Cazas et al 2004). In terms of drawing on the same empirical study, Vliegen and colleagues use the same sample and similar instruments (Vliegen et al, 2010;Vliegen et al 2013). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However the French version has more details on paternal disorders, drug treatments and past-history of both parents (Cazas et al 2004). In terms of drawing on the same empirical study, Vliegen and colleagues use the same sample and similar instruments (Vliegen et al, 2010;Vliegen et al 2013). …”
Section: Resultsmentioning
confidence: 99%
“…When specific MBUs were named in the 44 publications, it was evident that there are multiple sources collecting data from the same places: Bethlem Royal Hospital in South London, UK (Kenny et al 2013;Pawlby et al 2010;Seneviratne et al 2003), Wythenshawe Hospital in Manchester, UK (Antonysamy, Wieck, and Wittkowski 2009;Neil, Sanderson, and Wieck 2006), Austin Hospital in Melbourne, Australia (Bilszta, Buist, Wang, and Zulkefli 2012;, Helen Mayo House in Adelaide, Australia (Connerty et al 2015;Yelland et al 2015); and unnamed MBUs in Belgium (Vliegen et al 2010;Vliegen et al 2013) and Manchester in the UK (Wan, Salmon et al 2007;Wan, Warburton et al 2007; highlights that aside from the larger scale Marcé database information, studies focus on a small number of MBUs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,29,42,43 In the study by Holden and colleagues, 23 depression levels decreased below the cutoff for the treated mothers but not for the control sample (see Table 3). In the study by Milgrom and Beatrice, 39 a cutoff score for the Hamilton Depression Rating Scale (HDRS) was not reported.…”
Section: Severity Of Depressive Symptomatologymentioning
confidence: 90%
“…25,26,42,43 Howell and colleagues 35 found that chronically depressed mothers showed a smaller reduction in postpartum physical symptoms over time compared to the remitted group. This study also showed that the incidence of health problems in the infants, such as colic and illness, did not differ between remitted and chronic PPD mothers.…”
Section: Sociodemographic Differences Between Subgroupsmentioning
confidence: 99%